Complete metabolic response in FDG-PET-CT scan before discontinuation of immune checkpoint inhibitors correlates with long progression-free survival - Schank, Timo Emanuel; Forschner, Andrea; Sachse, Michael Max; Dimitrakopoulou-Strauss, Antonia; Sachpekidis, Christos; Stenzinger, Albrecht; Volckmar, Anna-Lena; Enk, Alexander; Hassel, Jessica C. (Cancers, 2021)
Checkpoint inhibitors have revolutionized the treatment of patients with metastasized melanoma. However, it remains unclear when to stop treatment. We retrospectively analyzed 45 patients (median age 64 years; 58% male) with metastasized melanoma from 3 cancer centers that received checkpoint inhibitors and discontinued therapy due to either immune-related adverse events or patient decision after an (18F)2-fluoro-2-deoxy-D-glucose positron emission tomography (FDG-PET) combined with a low-dose CT scan (FDG-PET-CT) scan without signs for disease progression. After a median of 21 (range 1-42) months of immunotherapy an FDG-PET-CT scan was performed to evaluate disease activity. In these, 32 patients (71%) showed a complete metabolic response (CMR) and 13 were classified as non-CMR. After a median follow-up of 34 (range 1-70) months, 3/32 (9%) of CMR patients and 6/13 (46%) of non-CMR patients had progressed (p = 0.007). Progression-free survival (PFS), as estimated from the date of last drug administration, was significantly longer among CMR patients than non-CMR (log-rank: p = 0.001; hazard ratio: 0.127; 95% CI: 0.032-0.511). Two-year PFS was 94% among CMR patients and 62% among non-CMR patients. Univariable Cox regression showed that metabolic response was the only parameter which predicted PFS (p = 0.004). Multivariate analysis revealed that metabolic response predicted disease progression (p = 0.008). In conclusion, our findings suggest that patients with CMR in an FDG-PET-CT scan may have a favorable outcome even if checkpoint inhibition is discontinued.